التوزيع الجغرافي للمساجد بمصراتة: الدائري الثالث نموذجاً (Journal of Academic Research, 2021)
This research study presented the geographical distribution of mosques in the municipality of Misrata, taking "the third ring” road as a model. The research introduction focused on the most important determinants that affect the spatial distribution of mosques. Geographical information systems (GIS) technology was used because of its role in reading the spatial distribution pattern of mosques on The geographical area, in addition to its distinctive role in the production and design of maps, which are the ideal means of explanation in analyzing, reading and understanding the distribution picture, and the results that are extracted through these maps of the results that support the research assumptions and the objectives to be reached.     The study also sought to conduct a field study in order to locate mosques and read their coordinates by means of a GPS device, and with the help of the data of the General Authority for Endowments and Islamic Affairs, their names and types were identified, and with the support of the produced maps, a group of elements that contribute to explaining the problem of the research and reaching the results were read and analyzed. And these elements began with the analysis of the geographical distribution area, which is the center of the study and its axis, through which the spatial distribution of the mosques in the study area became clear, followed by the analysis of the middle center, according to which the center point was determined from the total points of the phenomenon in the school "mosques", then comes the standard distance and through its analysis was done Identifying the extent of the divergence between the vocabulary of the phenomenon spatially, as for the impact of the service, which is the spatial boundaries that this service covers, it was intertwined and common in all points of the phenomenon, and to increase the clarification, the study area was divided into four sectors, including the characteristics of each sector separately.     The study also investigated the criterion for the distance between mosques from the Islamic legal point. Findings indicate that most of the jurisprudential opinions were of the opinions that there is a lack of a specific distance. The construction and expansion of mosques depends on the needs and requirements of the population.     Finally, the study presented a set of findings and recommendations, and among these results, the geographical distribution of mosques in the study area is dominated by the character of randomness and irregularity, in addition to the fact that their distribution is not subject to planning criteria, which caused a large overlap in the scope of the service of each mosque. As for the recommendations, it was Among them: Work to develop planning standards that regulate the construction of mosques and the selection of appropriate sites with the actual participation of the geographer and the technology of geographic information systems (GIS). A recommendation was directed to the General Authority for Endowments and Islamic Affairs to set a standard for the separation between mosques and generalize this to all municipalities and endowment departments. The researcher used to collect data and information with some scientific references and bulletins issued by the General Authority for Endowments and Islamic Affairs, in addition to the field study.